Inhibitory effects of some phenolic compounds on in vitro culture of Cercosporidium personatum - N. JAYABALAN, P. VENKATACHALAM and (Indian Phytopathology, 2002)
In vitro mycelial growth of Cercosporidium personatum (Phaeoisariopsis personata) was appreciably inhibited by phenolic compounds. Growth Inhibition increased with increase in the concentration of phenolic compounds. The degree of growth inhibition was dependent on the spatial arrangement around the benzene ring. Addition of a hydroxyl group generally decreased the growth inhibitory capacity of phenol. The relative toxicity was in the order phenol > catechol > pyrogallol > resorcinol > hydroquinone in both liquid and solid media. The inhibitory .effect of phenolic compounds was more pronounced with gelatin as N-source as compared to KNO_3.